Effectiveness Of Fertilizers Inorganic Micro Green Supe C On Tomato - Wahyu Handayati (Gontor AGROTECH Science Journal, 2016)
One component of farming technologies that play a role in efforts to increase the production of tomato plants is fertilization. Green Supe C leaf fertilizer containing some essential micronutrients that may increase the productivity of tomato plants. In this regard an experiment was conducted at Experimental Garden Karangploso BPTP East Java, from July to October 2015. The purpose of the study was to determine the effectiveness of micro fertilizer Green Supe C on growth, yield and economic feasibility on tomato plants. Experiments using a randomized block design with 9 treatments and 3 replications. As the treatment : A. Control (without inorganic fertilizer), B. Standard fertilizer 75 % (112.5 kg urea + 112.5 kg SP-36 + 75 kg KCl + 450 kg NPK Ponska), C. Standard fertilizer 75 % (112.5 kg urea + 112.5 kg SP-36 + 75 kg KCl + 450 kg NPK Ponska + 2 cc Green Supe C), D. Standard fertilizer 75 % (112.5 kg urea + 112.5 kg SP-36 + 75 kg KCl + 450 kg NPK Ponska + 4 cc Green Supe C), E. Standard fertilizer 75 % (112.5 kg urea + 112.5 kg SP-36 + 75 kg KCl + 450 kg NPK Ponska + 6 cc Green Supe C), F.Standard fertilizer 100 % (150 kg urea + 150 kg SP-36 + 100 kg KCl + 600 kg NPK Ponska), G. Standard fertilizer 100 % (150 kg urea + 150 kg SP-36 + 100 kg KCl + 600 kg NPK Ponska + 2 cc Green Supe C), H. Standard fertilizer 100 % (150 kg urea + 150 kg SP-36 + 100 kg KCl + 600 kg NPK Ponska + 4 cc Green Supe C) dan I. Standard fertilizer 100 % (150 kg urea + 150 kg SP-36 + 100 kg KCl + 600 kg NPK Ponska + 6 cc Green Supe C). The study showed that the application of the micronutrient fertilizer Green Supe C can improve plant growth and crop yields compared to controls and standards without micro fertilizer. Applications Green Supe C at 6 cc / l in the standard fertilizer treatment (treatment I) gives the yield 41.94 t / ha that higher 4.90% than without micronutrient fertilizer (40.94 tons/ha). Farming using Green Supe C has a greater profit especially at doses of 6 cc/l standard (treatment I) with B/C ratio about 1.74 that compared to control and standard fertilizers i.e. 1.16 and 1.62. In financial terms, although there are additional costs for the purchase of fertilizer micronutrient Green Supe C aboutRp 136.000, but an increase in revenue up toRp 5.744.000